2010
DOI: 10.4236/jwarp.2010.23026
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Limited Ammonium Nitrogen and Water Temperature on the Urban Stream Restoration Using Bacterial Technology – View from the Perspective of Numerical Modelling

Abstract: To complete the previously information issued on the feasibility study and some technical challenges identified from the application of bacterial technology, this study presents another characteristics of numerical output as the bacterial growth is now also limited to ammonium nitrogen and water temperature. Based on the results obtained, it is found that the degradation of readily biodegradable COD will be much slower because of lower bacterial growth. At certain period, the COD concentration will increase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It also was found that, although the water is now clearer and contains aquatic life, there is still a considerable increase in the concentration of total phosphorus, total nitrogen, and ammonium-nitrogen. Using the same selected model parameters as presented previously by the same model in Yudianto and Xie (2010c) (Figure 5), because of the conversion of ammonium to nitrate before it increases, there will be a potential of some algae to appear during the treatment processes. Besides the ammonium-nitrogen, other parameters (i.e., particulate products from COD decay and particulate degradable organic nitrogen) also may increase after they reach their minimum concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also was found that, although the water is now clearer and contains aquatic life, there is still a considerable increase in the concentration of total phosphorus, total nitrogen, and ammonium-nitrogen. Using the same selected model parameters as presented previously by the same model in Yudianto and Xie (2010c) (Figure 5), because of the conversion of ammonium to nitrate before it increases, there will be a potential of some algae to appear during the treatment processes. Besides the ammonium-nitrogen, other parameters (i.e., particulate products from COD decay and particulate degradable organic nitrogen) also may increase after they reach their minimum concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Besides describing the practical setting of biological treatment implemented at the Xuxi River, to understand the relationships between bacterial growths, substrate removal, dissolved oxygen, and other forms of nitrogen in a stream, this study also includes verification of the developed numerical model. Basically, the model was developed based on combination of Streeter Phelps and some kinetics equations used in Activated Sludge Model No.1 (ASM-1) (Jeppsson, 1996) under certain circumstances of limiting parameters (Yudianto and Xie, 2010c). Although ASM-1 has been extended to broader forms, the original model probably is still the most widely used for describing biodegradation processes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these considerations, we can adopt the new technique as BT with complete confidence. Their bacteria are usually hired to vitiate pollutants or nutrients into simple or nontoxic entity and produce suitable effluents [ 16 ]. This technology has reassuring advantages compared to other traditional techniques as already discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined to be successful with reliable results in boosting up the recovery processes of all water bodies compared to the other traditional technologies. It extends for the rehabilitation of polluted lakes, rivers, and streams and is also reliable for the requirement of the wastewater effluent standards without constructing massive structures as compared to the other conventional methods [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%